Peripheral nerve stimulation and immunity: the expanding opportunities for providing mechanistic insight and therapeutic intervention. (8th September 2021) - Falvey, Aidan; Metz, Christine N; Tracey, Kevin J; Pavlov, Valentin A
Abstract: Pre-clinical research advances our understanding of the vagus nerve-mediated regulation of immunity and clinical trials successfully utilize electrical vagus nerve stimulation in the treatment of patients with inflammatory disorders. This symbiotic relationship between pre-clinical and clinical research exploring the vagus nerve-based 'inflammatory reflex' has substantially contributed to establishing the field of bioelectronic medicine. Recent studies identify a crosstalk between the vagus nerve and other neural circuitries in controlling inflammation and delineate new neural immunoregulatory pathways. Here we outline current mechanistic insights into the role of vagal and non-vagal neural pathways in neuro-immune communication and inflammatory regulation. We also provide a timely overview of expanding opportunities for bioelectronic neuromodulation in the treatment of various inflammatory disorders. Abstract : The role of peripheral nerves in immunity